2015
DOI: 10.7763/joebm.2015.v3.316
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Personality, Privacy Concerns and Usage of Location-Based Services (LBS)

Abstract: Abstract-This paper examines the effects of the Big Five personality traits on concern for information privacy (CFIP) and the effects of the formulated concern for information privacy towards perceived risk, which in turn determine location-based services (LBS) usage intention. Data for this research was collected from 291 users and non-users of LBS. Result from Pearson correlation analysis indicated significant relationships exist between: (1) extraversion, and openness with collection; (2) extraversion, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Given that these individuals’ heightened levels of cortical arousal lead to an increase in the use of stimuli-rich environments ( Wilson et al., 2010 ), such as Facebook, they may view privacy-related behaviors (e.g., configuring privacy settings) as a distracting exercise—that is, as failing to provide stimulation. Additionally, research has identified either a negative relationship between extraversion and privacy concerns ( Hin, 2015 ; Sharma and Jaswal, 2016 ) or no significant relationship ( Junglas et al., 2008 ; Osatuyi, 2015 ). It is thus likely that extraverts are less concerned about the privacy of their app-based information than others.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Given that these individuals’ heightened levels of cortical arousal lead to an increase in the use of stimuli-rich environments ( Wilson et al., 2010 ), such as Facebook, they may view privacy-related behaviors (e.g., configuring privacy settings) as a distracting exercise—that is, as failing to provide stimulation. Additionally, research has identified either a negative relationship between extraversion and privacy concerns ( Hin, 2015 ; Sharma and Jaswal, 2016 ) or no significant relationship ( Junglas et al., 2008 ; Osatuyi, 2015 ). It is thus likely that extraverts are less concerned about the privacy of their app-based information than others.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…According to the conclusion of Mouakket and Sun [ 49 ], extraversion also had a positive association with the utilitarian value of SNSs. There is a negative association between extraversion and privacy concern [ 48 , 58 , 59 ] or no significant relationship [ 40 , 50 , 60 ]. Furthermore, Walczuch and Lundgren [ 61 ] discovered a link between extraversion and trust in online services.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Morton (2013) estimates SEM on survey data from 353 students, and constructs two higher-order factors of personality traits, namely stability (agreeableness, conscientiousness, reversed neuroticism) and plasticity (openness, extraversion), concluding a negative impact of stability on concern about the privacy behavior of organizations and government. Hin et al (2015) analyze survey data from 291 adults in Malaysia using Pearson correlation. They divide concern for information privacy (CFIP) into four factors -collection, improper access, errors and secondary use -and further investigate the impact of personality traits on each factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Globally, it is expected that in 2020, e-sales will reach USD 4.1 trillion with their share in total retail sales doubling compared to the 2015 level (eMarketer, 2016). Another common theme of investigating online privacy concern is the issue of location-based services (Hin et al, 2015). The bulk of mobile phone applications, and especially social media, contain features which enable data to be collected on the users' whereabouts through GPS tracking.…”
Section: Introductionmentioning
confidence: 99%